Pengaruh Pembelajaran dengan Pendekatan Kontekstual terhadap Pemahaman Konsep Fisika - Aryani A Wahab; Amiruddin Hatibe; Muhammad Jarnawi (Jurnal Kreatif Online, 2021)
The purpose of this study was to determine whether there was an effect of learning with a contextual approach on students' understanding of physics concepts. The hypothesis proposed in this study was that there was an effect of contextual approach learning on understanding physics concepts in class VIII SMP 19 Palu. The population of this study were all eight graders of SMP 19 Palu. Sampling was carried out by purposive sampling with the research sample being class VIIIC as the control class and class VIIIA as the experimental class. The research instrument was in the form of a concept understanding test that has been validated by an expert validator. The results of data analysis from the score range between (0-100) obtained an average score of 63.13 for the experimental class with a standard deviation of 0.97 and 55.00 fpr the control class with a standard deviation of 2.12. Based on the hypothesis test, it showed that tcount > ttable was 6.46 > 1.67, with a significance level of =0.05, thus H1 was accepted and H0 was rejected. The test results proved that there was an influence on understanding the concept of physics between classes that take part in learning with a contextual approach and students who take part in conventional learning.